Perancangan Antena Mikrostrip Circular Dual Band 28/38 GHz Dengan Metamaterial CSRR Untuk Jaringan Komunikasi 5G - Hidayatul Amin; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Communication technology development are growing to the 5G era, where there is a significant increase in performance compared to previous generations. The occurrence of improvement and mobile wireless service in the future, there are still some issues that can not be accommodated even by today's 4G, such as high data rates, area coverage and low energy consumption. Therefore, 5G technology will solve the problem and the need to improve efficiency and network capacity, increase data rate with better coverage on low power consumption. This research will design microstrip antenna MIMO (multiple input multiple output) 4x4 with Metamaterial CSRR (Complementary Split-Ring Resonator), which works at a frequency of 28 GHz and 38 GHz using CST Microwave Studio software, The antenna is designed by using RT-duroid 5880 substrate with a thickness of 1.575 mm. The simulation results obtained for MIMO 4x4 are the return loss value of -25.916 dB and -25.697, the bandwidth for frequency 28 is 15.89% (4.45 GHz) and frequency of 38 5.92% (2.25 GHz), VSWR (Voltage Standing Wave Ratio) ≤ 1.106 and ≤ 1.109 and gain ≥ 10,5 dBi.Keywords: Return loss, Bandwidth, VSWR, gain